Spontaneous remission of choroidal involvement by chronic myelomonocytic leukemia: a case report - Diral, Elisa; Catalano, Gloria; Cicinelli, Maria Vittoria; Distefano, Andrea; Mastaglio, Sara; Vago, Luca; Lupo Stanghellini, Maria Teresa; Bernardi, Massimo; Ponzoni, Maurilio; Ciceri, Fabio; Carrabba, Matteo G. (Frontiers in Oncology, 2024)
Chronic myelomonocytic leukemia (CMML) is a rare hematological disorder characterized by variable risk of evolution to acute myeloid leukemia; to date, allogeneic stem cell transplantation is the only curative treatment. We report a case of choroidal involvement in a woman affected by CMML and presenting only with visual impairment. The patient was initially evaluated for an intensive therapeutic approach, but after biopsy the ocular lesion spontaneously regressed. Thus a “watch and wait” strategy was preferred. One year and a half after initial diagnosis, the patient is alive, with stable hematological disease and without any ocular involvement. Therefore, a close, not invasive follow up could be useful to tailor treatment for patients affected by single ocular lesions in CMML.